Sanitation, Settlements, and Disease: Public Health Management in the Semarang Gemeente, 1906–1942 - Kamiludin Kamiludin; Wasino Wasino (Tarikhuna: Journal of History and History Education, 2025)
This research examines the dynamics of public health, sanitation, and settlements in Gemeente Semarang during the period of 1906–1942, when rapid urbanization gave rise to various social and environmental issues. The focus of the research is directed toward how settlement conditions and sanitation systems were at the beginning of the Gemeente's formation, how disease outbreaks spread within that context, and how the colonial government responded through health management policies and kampung improvement. The primary objective of this research is to historically reconstruct the linkage between urban spatial planning, sanitation, and the emergence of disease outbreaks in Semarang. The method used is the historical research method with the stages of heuristics, source criticism, interpretation, and historiography. This research utilizes several primary sources such as Van Wonen en Bewonen (1913), De Locomotief (15 January 1908), Bataviaasch Nieuwsblad (22 July 1918), Verslag van den toestand der gemeente Semarang (1918–1930), Gedenkboek Semarang (1931), as well as archives from the Koninklijke Bibliotheek and KITLV Netherlands. The results of the study show that the urbanization process caused spatial inequality between organized European settlements and indigenous kampungs that were crowded and unhygienic. This condition triggered the spread of cholera, malaria, influenza, plague, and dysentery outbreaks, with high mortality rates among the indigenous population. As a response, the Gemeente Semarang government implemented public health policies through the construction of a rioleering (sewerage) system (1913–1923) and the kampongverbetering (kampung improvement) program (1917–1938) which were oriented toward environmental improvement and social facilities.